2015
DOI: 10.14710/ik.ijms.19.4.189-194
|View full text |Cite
|
Sign up to set email alerts
|

Sebaran Material Organik dan Zat Hara Oleh Arus Pasang Surut di Muara Sungai Demaan, Jepara (The Distribution of Organic Matter and Nutrients by Tidal Current at Demaan Estuary, Jepara)

Abstract: The Distribution of Organic Matter and Nutrients by Tidal Current at Demaan Estuary, JeparaThe distribution of organic matter and nutrients in the estuary can be influenced by tidal current.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
0
0
2
Order By: Relevance
“…A similar pattern was found for phosphate nutrients, except for Jepara waters which were found at station 6 which is located near land. Through the Theoretical Dilution Line (TDL) approach between nutrients and salinity, rivers make the main contribution as a source of nutrients in coastal waters [Maslukah et al, 2014]. Based on Table 1, using the ratio of values from each location, we found that the distribution of Chl-a is closely related to the nutrients including N, P, and the N/P ratio (stoichiometry ratio).…”
Section: Discussionmentioning
confidence: 95%
“…A similar pattern was found for phosphate nutrients, except for Jepara waters which were found at station 6 which is located near land. Through the Theoretical Dilution Line (TDL) approach between nutrients and salinity, rivers make the main contribution as a source of nutrients in coastal waters [Maslukah et al, 2014]. Based on Table 1, using the ratio of values from each location, we found that the distribution of Chl-a is closely related to the nutrients including N, P, and the N/P ratio (stoichiometry ratio).…”
Section: Discussionmentioning
confidence: 95%
“…Selain dari industri batik, limbah organik juga bersumber dari aktivitas manusia, seperti detergen dan air mandi. Input bahan organik dapat meningkatkan kesuburan perairan akibat masukan nutrien, salah satunya P (Maslukah et al 2014). keberadaan nutrien di suatu perairan akan sangat berpengaruh pada pertumbuhan organisme di air, salah satunya fitoplankton.…”
Section: Pendahuluanunclassified
“…Kesuburan perairan berperan penting dalam pertumbuhan biota laut dalam rentang kondisi tertentu (baku mutu yang ditetapkan yaitu Kepmen LH No. 51/2004 tentang baku Mutu air Laut), yaitu ketika mencapai mencapai kondisi kesuburan perairan optimum, maka biota laut dapat tumbuh secara optimal dengan ketersediaan plankton yang cukup, sebaliknya apabila perairan terlalu subur (eutrofik) melebihi baku mutu yang ditetapkan akan berdampak pada terjadinya alga blooming yang mempengaruhi berkurangnya oksigen terlarut (dissolved oxigen) secara signifikan yang berefek pada meninggalnya ikan secara massal, selain itu dapat memicu munculnya zat beracun antara lain seperti nitrit, amonia dan hidrogen sulfida (H2S) akibat penguraian secara anaerob (Maslukah et al, 2014a).…”
Section: Pendahuluanunclassified